Chemical compositions, anti-oxidant and anti-inflammatory potential of ethanol extract from Zhuke-Hulu tea. (December 2021) - Zong, Shuai; Wang, Helin; Li, Jinglei; Liu, Jun; Jin, Changhai
Abstract: Zhuke-Hulu tea is an herbal tea widely enjoyed by people in Southern China. For the first time the phytochemical compositions of Zhuke-Hulu tea ethanol extract (ZHTE) were analyzed by GC-MS and UPLC-ESI-MS/MS, and the anti-oxidant and anti-inflammatory activities were evaluated. Several categories of substances in ZHTE were identified, among which organic acids, phenolics/phenolic acids and flavonoids were the major components. ZHTE showed significant anti-oxidant activity as measured by free radical scavenging assays and reducing power test. Moreover, ZHTE exhibited cytoprotective effect against H2 O2 -induced oxidative stress damage by enhancing endogenous anti-oxidant defense system and Nrf2 nuclear translocation. In addition, ZHTE also exerted anti-inflammatory efficiency by down-regulating the protein levels of iNOS and COX-2 as well as the production of pro-inflammatory cytokines. In parallel, ZHTE alleviated intestinal inflammation induced by dextran sulfate sodium (DSS) through reducing pro-inflammatory cytokines level, inhibiting inflammatory cell infiltration, and modulating gut microbiota. These findings provide a solid foundation for the nutraceutical benefits of Zhuke-Hulu tea and promote its consumption as a functional beverage. Graphical abstract: Image 1 Highlights: Phytochemical profile of Zhuke-hulu tea ethanol extract (ZHTE) was firstly analyzed. Organic acids, polyphenols and flavonoids were the major components of ZHTE. ZHTE showed significant anti-oxidant and anti-inflammatory activities. ZHTE showed remarkable cytoprotective effect against oxidative stress damage. Anti-colitis effect of ZHTE was related to the regulation of gut microorganisms.